The Evolution of ICT (Docentes 2.0 Journal, 2013)
From this we can denote how the use of ICT education has evolved where we thought it would not be less and that in turn it can be encouraged and now we can see how professionals in this field use these new ICTs in the Daily development of Labor as teachers with very good results. At the International Education Conference held in Geneva in 2001 called "Education for all to learn to live together" already referred to the importance that these new ICTs would have in the educational field according to the changes that our societies are experiencing Modern There is a notable interest in the educational community in the teaching use of these ICTs.
Keywords: ICT; Evolution